GALAH survey: chemically tagging the thick disk. Issue 67 (17th July 2015) - Bland-Hawthorn, J.; Sharma, S.; Freeman, K.
Abstract : The GALAH survey targets one million stars in the southern hemisphere down to a limiting magnitude of V = 14 at the Anglo-Australian Telescope. The project aims to measure up to 30 elemental abundances and radial velocities (≈1 km s −1 accuracy) for each star at a resolution of R = 28, 000. These elements fall into 8 independent groups ( e.g. α, Fe peak, r-process). For all stars, Gaia will provide distances to 1% and transverse velocities to 1 km s −1 or better, giving us a 14D set of parameters for each star, i.e. 6D phase space and 8D abundance space. There are many scientific applications but here we focus on the prospect of chemically tagging the thick disk and making a direct measurement of how stellar migration evolves with cosmic time.